2011
DOI: 10.1002/jts.20638
|View full text |Cite
|
Sign up to set email alerts
|

Teacher‐delivered resilience‐focused intervention in schools with traumatized children following the second Lebanon war

Abstract: The 2006 Lebanon War exposed children in the north of Israel to daily rocket attacks. To cope with the massive psychological needs, a teacher-delivered protocol focusing on enhancing personal resilience was implemented. Children were assessed for risk factors, symptoms, and adaptation before the 16-week program (Time 1; n = 983) and after its completion (Time 2; n = 563). At a 3-month follow-up (Time 3; n = 754) children were assessed together with a waiting-list comparison group (n = 1,152). Participating chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(50 citation statements)
references
References 32 publications
5
43
0
2
Order By: Relevance
“…Unlike most strife that is preceded and followed by a period of increased tension, disruption and fearful events, the Lebanon war erupted unexpectedly as a missile bombardment on the north of Israel, and ceased equally abruptly 34 days later after which near normal life was restored almost immediately (LevWiesel et al 2008;Wolmer et al 2011). Moreover, the type of threat was primarily circumscribed to missile bombardment, of which some 4000 landed in the northern region of Israel; there was little fear of enemy invasion and basic services were minimally disrupted.…”
Section: The Current Studymentioning
confidence: 97%
“…Unlike most strife that is preceded and followed by a period of increased tension, disruption and fearful events, the Lebanon war erupted unexpectedly as a missile bombardment on the north of Israel, and ceased equally abruptly 34 days later after which near normal life was restored almost immediately (LevWiesel et al 2008;Wolmer et al 2011). Moreover, the type of threat was primarily circumscribed to missile bombardment, of which some 4000 landed in the northern region of Israel; there was little fear of enemy invasion and basic services were minimally disrupted.…”
Section: The Current Studymentioning
confidence: 97%
“…The large number of hours that teachers spend with children each week enables them to identify posttraumatic behavior change. If knowledgeable, they can also provide coping assistance including emotional processing, distraction, and the reinstitution of familiar roles and routines (Prinstein, La Greca, Vernberg, & Silverman, 1996 Although a number of studies have shown the positive effects of teacher-mediated interventions related to mass-trauma such as war and disaster (e.g., Wolmer, Hamiel, Barchas, Slone, & Laor, 2011;, little is known about teachers' support of children in daily school life who have been exposed to a variety of traumatic events. An unpublished qualitative study (Alisic, 2011) suggested that elementary school teachers are uncertain about their role and about what to do to assist children effectively after traumatic exposure.…”
mentioning
confidence: 99%
“…Because most societies lack the resources required to individually assist masses of children, post-disaster therapeutic approaches may require a group format, such as universal teacher-delivered interventions in the kindergarten setting 35,36,37 . Supported by the trusting relations with children and parents, these non-stigmatic interventions have been found to effectively reduce the post-exposure suffering of school-age children following natural disasters and wars 35,36,37,38,39 .…”
Section: Interventionsmentioning
confidence: 99%
“…Supported by the trusting relations with children and parents, these non-stigmatic interventions have been found to effectively reduce the post-exposure suffering of school-age children following natural disasters and wars 35,36,37,38,39 . However, for the most symptomatic preschoolers, group interventions may not be sufficient to alleviate their suffering.…”
Section: Interventionsmentioning
confidence: 99%